Political Dynamics of Muhammadiyah and Its Relevance to the Concept of the State in Islam - Bakry, Kasman; Asse, Ambo; Syamsuddin, Darussalam; Salenda, Kasjim; Shaari, Roziana (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study describes the political dynamics of Muhammadiyah and its relevance to the constitutional concept from Islamic political perspective. This research uses descriptive, and historical approach. The results of the study finds out: First, the characteristics of an Islamic state are applying God's law, adopting a form of leadership, being universal, not totalitarian, and applying a humane leadership pattern. This character is supported by a leadership system based on basic principles in the Islamic state (al-mabda 'al-asāsī fi dawlah al-Islamiyyah) which includes: trustworthiness (al-amānah), deliberation (al-syūrā), equality (al- musāwā), justice (al-'adālah), and plurality (al-ta 'addudiyya). Second, the Muhammadiyah doctrine originates from the al-Qur'an and al-Hadith and contains a system of beliefs, thoughts, and actions which, as a whole, is accumulated into the ideology and values of the Muhammadiyah movement. This doctrine is then outlined in Muhammadiyah's statute and Bylaws (AD/ART) and covers all steps and strategies for the struggle, personality, beliefs and way of life of Muhammadiyah. Third, political theology and universal and fundamental religious understanding serve as guidelines, and at the same time, as the blueprint for Muhammadiyah's political midset which is implemented through political and cultural channels in the realm of high, allocative politics.